Preferences for gene therapy in Duchenne muscular dystrophy: insights from patient and caregiver interviews and attribute development - Desmet, Thomas; Van Haesendonck, Lauren; Vermeire, Sophie; van Overbeeke, Eline; Simoens, Steven; Huys, Isabelle (Frontiers in Pharmacology, 2025)
BackgroundDuchenne muscular dystrophy (DMD) is an X-linked degenerative muscle disease with no curative treatment available to date. The current long-term use of corticosteroids is associated with severe adverse effects. With the progress of promising gene therapy for DMD, this research aims to identify the key characteristics that matter most to patients, develop attributes for a subsequent quantitative preference study, ultimately aimed to inform future market access and clinical decision-making on gene therapy.MethodsA literature review was conducted, followed by semi-structured interviews with DMD patients and caregivers to explore their preferences regarding DMD treatment benefits and side effects and gene therapy as a promising treatment option. A ranking exercise helped reveal the most important treatment characteristics, forming the basis for the first step of a structured, four-step attribute and level development process: (1) attribute identification, (2) attribute selection, (3) attribute description, and (4) level development. The forthcoming six attributes and levels were determined by applying six inclusion and exclusion criteria aligned with PREFER guidelines and reaching consensus within an international multidisciplinary advisory board comprising patient representatives, clinicians, and preference method experts.ResultsA total of thirteen interviews were conducted with seven DMD patients and eleven caregivers. The literature review and interviews resulted in the identification of 48 unique disease and treatment characteristics. Furthermore, they revealed a high willingness of caregivers of especially younger children to consider gene therapy in a clinical trial setting, and that the primary treatment characteristics valued by patients and caregivers are related to muscle and heart function, and the impact on self-care activities, independence. The final attributes are patient-friendly, clinically relevant and meaningful to patients, with descriptions that are as brief as possible: the type of therapy, effect on life expectancy, risk of life-threatening side effects related to the therapy, years that ventilatory support can be postponed, number of years maintaining current physical functioning, and years and number of patients in which that therapy has been studied.ConclusionThis study identified the treatment characteristics most important to DMD patients and their caregivers and translated them into six key attributes with corresponding levels. It underscores the practical value of qualitative research and patient engagement in ensuring that attributes and level development for future quantitative preference elicitation studies remain clinically relevant and aligned with patient priorities.